Identification of trombiculid mites (Acari: Trombiculidae) on rodents from Chiloé Island and molecular evidence of infection with Orientia species - Acosta-Jamett, Gerardo; Martínez-Valdebenito, Constanza; Beltrami, Esperanza; Silva-de La Fuente, María Carolina; Jiang, Ju; Richards, Allen L.; Weitzel, Thomas; Abarca, Katia (PLOS Neglected Tropical Diseases, 2020)
Background Scrub typhus is an emerging vector-borne zoonosis, caused by Orientia spp. and transmitted by larvae of trombiculid mites, called chiggers. It mainly occurs within a region of the Asia-Pacific called the tsutsugamushi triangle, where rodents are known as the most relevant hosts for the trombiculid vector. However, the reservoir(s) and vector(s) of the scrub typhus outside Asia-Pacific are unknown. The disease has recently been discovered on and is considered endemic for Chiloé Island in southern Chile. The aim of the present work was to detect and determine the prevalence of chiggers on different rodent species captured in probable sites for the transmission of orientiae responsible for scrub typhus on Chiloé Island in southern Chile and to molecularly examine collected chiggers for the presence of Orientia DNA. Methodology/Principal findings During the austral summer 2018, rodents were live-trapped in six sites and examined for chigger infestation. All study sites were rural areas on Chiloé Island, previously identified as probable localities where human cases acquired the scrub typhus. During a total of 4,713 trap-nights, 244 rodents of seven species were captured: the most abundant was Abrothrix olivacea. Chiggers were detected on all seven rodent species with a 55% prevalence rate. Chiggers showed low host specificity and varied according to site specific host abundance. Three genera of trombiculids were identified. Herpetacarus was the most abundant genus (93%), prevalent in five of the six sites. Infestation rates showed site specific differences, which were statistically significant using a GLM model with binomial errors. Molecular analyses proved that 21 of 133 (15.8%) mite pools were positive for Orientia species, all of them belonged to the genus Herpetacarus. Conclusions/Significance This study firstly reports the presence of different rodent-associated chigger mites positive for Orientia sp., in a region endemic for scrub typhus in southern Chile. Herpetacarus and two other genera of mites were found with high infestation rates of rodents in sites previously identified as probable exposure of scrub typhus cases. A substantial percentage of mite pools were positive for Orientia DNA, suggesting that chigger mites serve as vectors and reservoirs of this emerging zoonosis in South America.